THE IMPACT MODEL OF DEMOGRAPHIC INDICATORS ON INTERNET MARKETING PROCESSES - Kamala Hashimova (Problems of Information Society)
The organization of advertising and marketing by widely using the capabilities of the Internet has paved the way for the successful solution of economic processes. The use of demographic indicators to increase the efficiency of online advertising and marketing activities is a relevant and important issue to solve. This article determines the options of new campaigns to be conducted based on the personal data of online advertising and marketing users. The use of demographic indicators of customers for the study of marketing or public opinion creates conditions for identifying a specific consumer market. The article proposes a new model for the successful implementation of advertising and marketing based on the analysis of demographic indicators. This enables to adapt marketing messages and offers to specific population groups, increase their relevance and effectiveness. The impact of demographic indicators on advertising and marketing strategies can be useful for attracting new customers and can lead to an increase in the number of customers in sales. The article examines the theoretical aspects of using demographic data in Internet marketing and proposes a model for increasing the effectiveness of advertising campaigns. An analysis of existing research identifies the main factors affecting the effectiveness of marketing. The results of the study can be used by marketers to optimize their strategies and increase their competitiveness.